Lead Drives Complex Dynamics of a Conjugative Plasmid in a Bacterial Community - Cyriaque, Valentine; Madsen, Jonas Stenløkke; Fievez, Laurence; Leroy, Baptiste; Hansen, Lars H.; Bureau, Fabrice; Sørensen, Søren J.; Wattiez, Ruddy (Frontiers in Microbiology, 2021)
Plasmids carrying metal resistance genes (MRGs) have been suggested to be key ecological players in the adaptation of metal-impacted microbial communities making them promising drivers of bio-remediation processes. However, the impact of metals on plasmid-mediated spread of MRGs through selection, plasmid loss and transfer is far from being fully understood. In the present study, we used two-member bacterial communities to test the impact of lead on the dispersal of the IncP plasmid pKJK5 from a Pseudomonas putida KT2440 plasmid donor and two distinct recipients, Variovorax paradoxus B4 or Delftia acidovorans SPH-1 after 4 and 10 days of mating. Two versions of the plasmid were used, carrying or not carrying the lead-resistance pbrTRABCD operon, to assess the importance of fitness benefit and conjugative potential for the dispersal of the plasmid. The spread dynamics of metal resistance conveyed by the conjugative plasmid were dependent on the recipient and the lead concentration: For V. paradoxus the pbr operon did not facilitate neither lead resistance nor variation in plasmid spread. The growth gain brought by the pbr operon to D. acidovorans SPH-1 and P. putida KT2440 at Pb 1 mM enhanced the spread of the plasmid. At Pb 1.5 mM after 4 days, proteomics results revealed an oxidative stress response, an increased abundance of pKJK5 encoded conjugation and partitioning proteins, which most likely increased the transfer of the control plasmid to D. acidovorans SPH-1 and ensured plasmid maintenance. As a consequence, we observed an increased spread of pKJK5-gfp. Conversely, the pbr operon reduced the oxidative stress response, impeded the rise of conjugation and partitioning associated proteins, which slowed down the spread of the pbr carrying plasmid. Ultimately, when a fitness gain was recorded in the recipient strain, the spread of MRG carrying plasmids was facilitated through positive selection at intermediate metal concentration, while high lead concentration induced an oxidative-stress with positive impacts on proteins encoding plasmid conjugation and partitioning.